Plasmodium simium: birth and evolution of a zoonotic malaria parasite species - Nathalia Rammé M. de Albuquerque; Winni A. Ladeia; Ryan J. Scalsky; Ankit Dwivedi; Thomas C. Stabler; Priscila T. Rodrigues; Thaís C. de Oliveira; Joana C. Silva; Marcelo U. Ferreira (Parasitology)
Plasmodium simium, a parasite of platyrrhine monkeys, is known to cause human malaria outbreaks in Southeast Brazil. It has been hypothesized that, upon the introduction of Plasmodium vivax into the Americas at the time of the European colonization, the human parasite adapted to neotropical anophelines of the Kerteszia subgenus and to local monkeys, along the Atlantic coast of Brazil, to give rise to a sister species, P. simium. Here, to obtain new insights into the origins and adaptation of P. simium to new hosts, we analysed whole-genome sequence (WGS) data from 31 P. simium isolates together with a global sequence dataset of 1086 P. vivax isolates. Population genomic analyses revealed that P. simium comprises a discrete parasite lineage with greatest genetic similarity to P. vivax populations from Latin America – especially those from the Amazon Basin of Brazil – and to ancient European P. vivax isolates, consistent with Brazil as the most likely birthplace of the species. We show that P. simium displays half the amount of nucleotide diversity of P. vivax from Latin America, as expected from its recent origin. We identified pairs of sympatric P. simium isolates from monkeys and from humans as closely related as meiotic half-siblings, revealing ongoing zoonotic transmission of P. simium. Most critically, we show that P. simium currently causes most, and possibly all, malarial infections usually attributed to P. vivax along the Serra do Mar Mountain Range of Southeast Brazil.